Relationship between body mass index and gastroesophageal reflux disease in Mosul City - Waleed Khalid Mohammed Alhamoud; Noori Tauma Mahmood (Genius Journals, 2023)
The gastro-esophageal reflux disease (GERD) considered as a diagnostic and therapeutic challenge. Its incidence is increasing parallel with obesity worldwide. This study tried to find a correlation between the disease and body mass index (BMI).
Keywords: GERD symptoms; body mass index; endoscopic findings